MENU ENGINEERING SEBAGAI LANGKAH PENETAPAN STRATEGI PEMASARAN PADA RESTORAN SARI LAUT RESTU BALI - MADE MERTA (SOCA: Jurnal Sosial Ekonomi Pertanian, 2005)
Engineering Menu Method so called “Unique Method of Menu Analysis andDesign” try to answer the probloms faced by restaurant entrepreneur. This methodimplemeted in “Food Service Operation” in many famous restaurant in the world. Result ofthe research indicated that: (1) The existence menu at Dewi restu Bali restaurant effecttoward achieved food sell target, (2) There are three items of sum menu that analysis isDiod kategory, 5 menu include Plowhorse and 2 menu include Pizzle, and only 5 menuinclude Star kategory. Based on this result of analysis, so the market strategi have toimplemented, are: (a) For Stara kategory through to increase of sell price graduaaly, (b)Plowhorse menu kategory need to see competitor condition, material price and competitorsell price, before to increase the sell price, (c) For Puzzle menu kategory to increase thesell volume only can conducted with increase promotion more selectively, (d) Dog menukategory will give burden to the the other menu, and (e) The restoran should conductEngeneering menu periodically.